Pengaruh E-Service Quality, Customer Experience, dan Perceived Value terhadap Behavioral Intention pada Pengguna Grab di Kota Semarang - Aulia Nurputtik Puspita Dewi; Naili Farida; Sudharto Prawata Hadi (Jurnal Ilmu Administrasi Bisnis, 2024)
Abstract: The development of technology through the internet has led to changes in the lifestyle of Indonesians in terms of transportation. Grab is one of the ride hailing companies that is actively used by Indonesians. In 2020-2021 the number of users outperformed Gojek, Maxim, and InDrive. However, in 2022 Grab experienced a decrease in users of 9.1%. This study was conducted to determine the effect of E-Service Quality, Customer Experience, and Perceived Value on Behavioral Intention for Grab users in Semarang City. The sample size was 100 respondents with non-probability sampling technique, namely purposive sampling. Data collection techniques through questionnaires and literature studies. The type of research is explanatory research with a quantitative approach and is processed using SPPS for windows 25.0 software. The results showed that E-Service Quality has a positive and significant effect on Behavioral Intention, Customer Experience has a positive and significant effect on Behavioral Intention, Perceived Value has a positive and significant effect on Behavioral Intention, E-Service Quality, Customer Experience, and Perceived Value have a positive and significant effect simultaneously on Behavioral Intention. Based on the research results, suggestions that can be given by Grab need to improve service efficiency to be more responsive, innovate by collaborating with other companies, and improve user interaction. Suggestions for future researchers can expand the research locus by including Semarang Regency and adding satisfaction variables as intervening variables.Keywords: e-service quality; customer experience; perceived value; behavioral intentionAbstraksi: Perkembangan teknologi melalui internet menyebabkan perubahan gaya hidup masyarakat Indonesia dalam hal transportasi. Grab merupakan salah satu perusahaan ride hailing yang aktif digunakan masyarakat Indonesia. Pada tahun 2020-2021 jumlah penggunanya mengungguli Gojek, Maxim, dan InDrive. Namun, pada tahun 2022 Grab mengalami penurunan pengguna sebesar 9,1%. Penelitian ini dilakukan untuk mengetahui pengaruh E-Service Quality, Customer Experience, dan Perceived Value terhadap Behavioral Intention pada pengguna Grab di Kota Semarang. Jumlah sampel sebanyak 100 responden dengan teknik pengambilan sampel non-probability sampling, yaitu purposive sampling. Teknik pengumpulan data melalui kuesioner dan studi pustaka. Tipe penelitian berupa penelitian explanatory dengan pendekatan kuantitatif dan diolah menggunakan software SPPS for windows 25.0. Hasil penelitian menunjukkan E-Service Quality berpengaruh positif dan signifikan terhadap Behavioral Intention, Customer Experience berpengaruh positif dan signifikan terhadap Behavioral Intention, Perceived Value berpengaruh positif dan signifikan terhadap Behavioral Intention, E-Service Quality, Customer Experience, dan Perceived Value berpengaruh positif dan signifikan secara simultan terhadap Behavioral Intention. Berdasarkan hasil penelitian, saran yang dapat diberikan Grab perlu meningkatkan efisiensi pelayanan menjadi lebih responsif, melakukan inovasi dengan cara menjalin kerja sama dengan perusahaan lain, serta meningkatkan interaksi penggunanya. Saran untuk peneliti selanjutnya dapat memperluas locus penelitian dengan mengikutsertakan Kabupaten Semarang dan menambahkan variabel satisfaction sebagai variabel intervening.Kata Kunci: e-service quality; customer experience; perceived value; behavioral intention